KUALITAS SUMBER DAYA KEPEMIMPINAN DAN KUALITAS PRODUK DALAM UPAYA PENINGKATAN DAYA SAING UKM TENUN SUTERA SENGKANG - Yusran Yusran; Jannati Tangngisalu (Pascasarjana Universitas Halu Oleo, 2020)
The development of the Sengkang silk weaving SME industry in Wajo District has experienced ups and downs due to the ability of its resources and the ability to produce quality products but technological limitations that have an impact on increasing the competitiveness of the Sengkang silk weaving SME industry in the global market. From this, the objectives of this research are (1) To find out and analyze the quality of leadership resources on the competitiveness of Sengkang silk weaving SMEs, (2) To find out and analyze product quality on the competitiveness of Sengkang silk weaving UKM, and (3) To analyze the quality of leadership resources and product quality simultaneously on Sengkang silk weaving SMEs.The research sample of 30 respondents from a total population of 152 SMEs using a minimum sample of 15 questionnaire statements. The analytical method uses Multiple Linear Regression with the help of SPSS 22.0 application. Hypothesis test results in this study: (1) There is a positive and significant relationship between the quality of leadership resources on competitiveness, (2) There is a positive and significant relationship between product quality on competitiveness, (3) Product quality as the most dominant variable influencing on the competitiveness of Sengkang silk weaving SMEs.